Regulation and planning practices, institutions, agency - Beauregard, Robert A.; Cremaschi, Marco; Rydin, Yvonne 1957-; Lieto, Laura (Routledge, 2022)
"In Regulation and Planning, planning scholars from the UK, France, Italy, Sweden, Canada, Australia, and the United States explore how planning regulations are negotiated amid layers of normative considerations. It treats regulation not simply as a set of legal guidelines to be compared against proposed actions, but as a social practice in which issues of governmental legitimacy, cultural understandings, materiality, and power are contested. Each chapter addresses an actual instance of planning regulation including, among others, a dispute about a proposed Apple store in a public park in Stockholm, the procedures by which building codes are managed by planners in Napoli, the role that design plays in regulating the use of public space in a new Paris neighbourhood, and the influence of plans on the regulation of development in Malmö and Cambridge. Collectively, the volume probes the institutions and practices that give meaning and consequence to planning regulations. For planning students learning about what it means to plan, planning researchers striving to understand the influence of planners on urban development, and planning practitioners interested in reflecting on practices that occupy a great deal of their time, this is an indispensable book"--